SOSIALISASI PENGGUNAAN YOUTUBE YANG SEHAT DAN BAIK BAGI MURID SD DHARMA KARYA UT, TANGERANG SELATAN - Ayuningtyas, Fitria; Abdullah, Ahmad Zakki (Universitas Esa Unggul, 2019)
The background of this activity is the increasing use of the Internet among children. Not only it formed an opinion but shaping the culture at large. The term of Ã¢â‚¬Å“social mediaÃ¢â‚¬Â and